PENGARUH KARAKTERISTIK ANGGARAN TERHADAP HUBUNGAN KOMITMEN DAN SENJANGAN ANGGARAN (Students' Journal of Accounting and Banking, 2012)
This study aims to determine and analyze the influence of budget goal clarity and participation in the budget to the budget gap with organizational commitment as a moderating variable in the Secretariat of the Central Java Province. Population are the managers of the various functions at the Regional Secretariat of the Central Java Province, some 162 people, with a sample of some 62 functional managers. The sampling technique used is a Proportional Stratified Random Sampling. Analysis tools used in this study were Moderating Regression Analysis. Based on the test results indicate that the clarity of the budget target of a positive effect on the budget gap, may mean that more and more clear and specific managers in preparing the budget, the more it will enhance the ability of managers to predict the onset of the budget gap. Budgetaryparticipation has a positive effect on the budget gap, can be interpreted that the higher involvement of the managers of the organization, the more it will enhance the ability of managers to predict the onset of the budget gap. Organizational commitment are able to moderate the negative relationship between the clarity of the budget target with the budget gap. Organizational commitment can moderate the negative relationship between the clarity of the budget target with the budget slack.Keywords: Clarity of budget targets, budgetary participation, organizational commitment and the budget slack